Physical properties of soursop (Annona Muricata) powder produced by spray drying - Khaidatul Hasni, Mohamad Alias @ Ayit (2009)
The growing of fruits is limited in many countries to certain seasons and localities. In order to meet the demand of the market throughout the year in all areas, the commodities are preserved using different techniques. Actually, this research, is a about soursop fruits. Soursop fruit does not travel well and is rarely available fresh in areas where it is not grown. Nutritionally, the soursop fruit is high in carbohydrates, particularly fructose and also contains significant amounts of vitamin C, vitamin B1, and vitamin B2. Parts of the soursop tree are used in natural medicine in the tropics, including the bark, leaves, roots, fruit, and fruit seeds. The fruit and fruit juice are taken for worms and parasites, to cool fevers, to increase mother's milk after childbirth, and as an astringent for diarrhea and dysentery. Spray drying has become the most important method for the dehydration of fluid foods such as juices. This study is undertaken to investigate the feasibility of spray drying of soursop juice and to evaluate the physical properties of the powder produced. Independent variables were: inlet air temperature (160–190 °C) and maltodextrin concentration (10–25% of total feed solution). Moisture content, hygroscopicity, process yield, solubility and dissolution were analyzed as responses. Powder moisture content and process yield were positively affected by inlet air temperature which is directly related to heat and mass transfer. Process yield was also negatively influenced by maltodextrin concentration. Powders hygroscopicity decreased with increasing maltodextrin concentration and decreasing temperature. Powders with lower moisture content were more hygroscopic, which is related to the greater water concentration gradient between the product and the surrounding air. The result shows the optimum condition for Inlet Air Temperature is 1700C. While for maltodextrin concentration is 10%.